#### Answer

See below for detailed proof.

#### Work Step by Step

As $v$ is inversely proportional to $\sqrt s$, a formula for $v$ would have this form: $$v=\frac{n}{\sqrt s}=ns^{-1/2}$$ with $n$ being a constant.
Acceleration $a$ is the derivative of $v$ with respect to $t$: $$a=\frac{dv}{dt}=\frac{dv}{ds}\frac{ds}{dt}$$ (The Chain Rule)
The derivative of $s$ with respect to $t$ equals $v$, so $$\frac{ds}{dt}=v=ns^{-1/2}$$
The derivative of $v$ with respect to $s$ equals $v'$, so $$\frac{dv}{ds}=(ns^{-1/2})'=-\frac{1}{2}ns^{-3/2}$$
Therefore, $$a=-\frac{1}{2}ns^{-3/2}ns^{-1/2}=-\frac{n^2s^{-2}}{2}=-\frac{n^2}{2s^2}$$
As a result, $a$ is inversely proportional to $s^2$.